W kręgu sprawy pod kryptonimem "Beta". Ludność ukraińska na Ziemi Lubuskiej w latach 1970-1980 w świetle materiałów Służby Bezpieczeństwa = In the circle of the affair of code name "Beta". Ukrainian population in Lubusz Land, 1970-1980, in the light of documents of the Security Service - Słabig, Arkadiusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Ukrainian population relocated in the territory of the Lubusz Land was the target of the intensiva control from the communist safety apparatus. This apparatus had custody of the whole population of the People`s Republic of Poland could not omit the environment involved in tragic events of the previous war, having numerous compatriots behind the "iron curtain" and, what is most important,trying to retain its national identity. Meanwhile, Polish authorities realised consequently the policy of assimilation which led to stabilisation of the Ukrainians in Western and Northern territories and also blended them in a single-ethnic society.
Keywords: mniejszość ukraińska - Polska; Ziemia Lubuska; Służba Bezpieczeństwa; historia; po 1944 r.